TRANSFORMASI DIGITAL DAN PENGARUHNYA TERHADAP ASPEK PASAR SERTA STRATEGI PEMASARAN MODERN - Adam Rizqi Yusuf; Indra Ahmad Fahrezi Dzil Karami; Raya Hatta Dilaga; Yasin Maulana (Media Riset Bisnis Manajemen Akuntansi, 2026)
Digital transformation has significantly reshaped market dynamics and modern marketing strategies. This study aims to examine the impact of digital technologies such as artificial intelligence, big data, and digital platforms on market aspects and marketing strategies through a literature review approach. The analysis shows that digital transformation influences changes in consumer behavior, intensifies competition through platform-based markets, and encourages the adoption of data-driven marketing strategies. Furthermore, modern marketing practices increasingly emphasize omnichannel approaches, personalization, and customer experience. The study concludes that digital transformation is a strategic necessity for organizations to remain competitive and recommends the integration of digital capabilities with human-centered marketing approaches.Keywords : Digital transformation,Artificial intelligence (AI),Big data, Digital platforms,Market dinamics,Modern marketing strategies.